KARAKTER RELIGIUS PADA ANAK USIA DINI (STUDI KASUS PEMBIASAAN BERDO’A SEBELUM DAN SESUDAH MELAKUKAN KEGIATAN BELAJAR DI SPS BOUGENVIL) KECAMATAN CIRACAP - Aam Hamidah; Ibnu Huri; Indra Zultiar (CV. ADIBA AISHA AMIRA, 2024)
What matters most about a person is their religious character. Developing one's religious character is an ongoing process that requires context. Character education, then, needs to start early so that it can take root and grow. Childhood is a wonderful time when children's minds are open and susceptible to new ideas, and as parents and teachers, we hope that all of our children have healthy brain development and grow into happy and successful people. Being well-rounded encompasses not only intellectual prowess and the ability to express oneself clearly, but also a robust spiritual intelligence that can be developed by early exposure to religious values, including regular prayer. Examining the practices of religious character development in the classroom at SPS Bougenvil in Ciracap Regency is the primary goal of this research. In this qualitative research method, a case study methodology is utilized. The location of the study was SPS Bougainvillea in the Ciracap District of the Sukabumi Regency in West Java. A total of ten first-year PAUD SPS Bougenvil students served as study participants. Previous studies' findings don't seem to be applicable; so, habituation and ongoing education are necessary to help kids become accustomed to it in their daily lives.